ANALYSIS OF STUDENTS’ READING SKILL USING MOBILE DEVICE DURING LEARNING-FROM-HOME IN THE POST PANDEMIC: ANALYSIS OF STUDENTS’ READING SKILL USING MOBILE DEVICE DURING IN THE POST PANDEMIC - Siregar, Alfitriani (Journal of Innovation Research and Knowledge, 2022)
The objective of study was an analysis of students’ reading skill using mobile device during learning-from-home policy in the post pandemic time. Method design of study conducted by using descriptive qualitative research. The population was 40 students at eighth of Junior High School in PAB 19 HELVETIA. Sample was 20 students consist of 12 girls and 8 boys in 2021/2022 the academic years used purposive sampling. The technique of data used three steps, were: 1.) Questionnaire, 2.) Test, 3.) Documentation. The results of study was the students reading test were nine (45%) who could read fluently, five students (10%) could read with good accuracy, five students (10%) could pronounce well, and seven students (35%) could read with good intonation. The total percentage of students’ reading skill of assessment aspects aloud (in the average) 25%. So, the researcher concluded 75 % students couldn’t read well and didn’t understand about English reading. It is meant that their English reading skill were poor when online learning using by mobile device during learning-from-home policy in the post pandemic time.